Second-Generation Cobas AmpliPrep/Cobas TaqMan HCV Quantitative Test for Viral Load Monitoring: a Novel Dual-Probe Assay Design - Zitzer, Heike (American Society for Microbiology, 2013)
Hepatitis C virus (HCV) RNA viral load (VL) monitoring is a well-established diagnostic tool for the management of chronic hepatitis C patients. HCV RNA VL results are used to make treatment decisions with the goal of therapy to achieve an undetectable VL result. Therefore, a sensitive assay with high specificity in detecting and accurately quantifying HCV RNA across genotypes is critical. Additionally, a lower sample volume requirement is desirable for the laboratory and the patient. This study evaluated the performance characteristics of a second-generation real-time PCR assay, the Cobas AmpliPrep/Cobas TaqMan HCV quantitative test, version 2.0 (CAP/CTM HCV test, v2.0), designed with a novel dual-probe approach and an optimized automated extraction and amplification procedure. The new assay demonstrated a limit of detection and lower limit of quantification of 15 IU/ml across all HCV genotypes and was linear from 15 to 100,000,000 IU/ml with high accuracy (<0.2-log(10) difference) and precision (standard deviation of 0.04 to 0.22 log(10)). A specificity of 100% was demonstrated with 600 HCV-seronegative specimens without cross-reactivity or interference. Correlation to the Cobas AmpliPrep/Cobas TaqMan HCV test (version 1) was good (n = 412 genotype 1 to 6 samples, R(2) = 0.88; R(2) = 0.94 without 105 genotype 4 samples). Paired plasma and serum samples showed similar performance (n = 25, R(2) = 0.99). The sample input volume was reduced from 1 to 0.65 ml in the second version. The CAP/CTM HCV test, v2.0, demonstrated excellent performance and sensitivity across all HCV genotypes with a smaller sample volume. The new HCV RNA VL assay has performance characteristics that make it suitable for use with currently available direct-acting antiviral agents.